The Impact of Food Fortification on Health and Nutrition - Thambidurai Bharath; Kandasamy Karthikeyan (International Journal of Nutritions, 2024)
This comprehensive study explores the critical role that food fortification plays in enhancing nutritional outcomes and overall health. Through an extensive review of existing literature, this article explores the diverse ways in which fortifying foods with essential nutrients positively influences public health. This analysis encompasses the benefits of fortification by addressing micronutrient deficiencies, promoting overall well-being, and preventing various health conditions. Food fortification is a pivotal intervention in the realm of public health nutrition, aiming to address nutrient deficiencies and enhance overall well-being. This analysis looks intently at the various methods that meals fortification impacts nutritional effects and typical fitness. By enriching commonly consumed foods with essential vitamins, minerals, and other nutrients, fortification strategies aim to fill gaps in dietary intake and improve nutritional status populations. The effectiveness of food fortification in tackling specific nutrient deficiencies has been extensively studied and validated. For example, fortification of salt with iodine has played a pivotal role in preventing iodine deficiency disorders, while fortifying staple grains with folic acid has significantly reduced the prevalence of neural tube defects. Moreover, fortification programs targeting iron, vitamin A, and other key nutrients have demonstrated positive impacts on maternal and child health, reducing the burden of anaemia and related complications. By facilitating access to micronutrients critical for growth, development, and disease prevention, fortification initiatives contribute to improved immune function, cognitive development, and overall quality of life. Additionally, fortification efforts have the potential to alleviate the burden of nutrition-related chronic diseases, such as osteoporosis and cardiovascular conditions, by ensuring adequate intake of key nutrients.
Keywords: Food Fortification; Malnutrition; NAFDC; micronutrient; nutrients